E-LEARNING: THE EMERGING TECHNOLOGIES IN INSTRUCTION - Njagi, Mercy Wanja (My University, 2019)
The digital revolution has triggered huge changes in how learners access, consume, discuss and share knowledge. E-learning encompasses a wide variety of online initiatives including utilizing electronic technologies to access educational curriculum. E-learning is being adopted as an additional method in the educational process for it extends and enrich the learning opportunities hence it is necessary for instructional designers to discover innovative ways to make e-learning more effective for learners. The e-learning is a more modern, efficient and flexible alternative thus there is need to shift to it. The researcher used mixed-method analysis of research articles to find out available and valid information on e-learning. Thus researcher conducted an extensive literature review to collect the communicable knowledge on e-learning from various sources where e-learning is analysed and discussed such as books and book chapters related to e-learning, academic and scientific journals and open virtual spaces by recognized authors. The paper reveals vital information on definitions of e-learning from the field of education and information and communication technology, myths and facts about e-learning, goals of e-learning, potential benefits and demerits of e-learning. The paper is designed to provide practitioners, instructional designers, researchers and policy makers with some insights about e- learning. The recommendations are drawn highlighting areas that academic scholars and researchers can do further research to increase the effectiveness and scalability of e-learning. It should be acknowledged that the information is by no means exhaustive but rather a starting point for critical and informative discussion on e-learning
Keywords: E-learning; Online Education; Electronic Technologies